Histopathological Alterations and Multidrug-Resistant Bacteria in Mugil cephalus from Polluted Tripoli Coastline, Libya - Elbahi, Asma; Bukha, Khawla; Mahgiubi, Shaima; Shlayek, Samira; Elyasir, Elham; Ahmed, Mohamed (AlQalam Journal of Medical and Applied Sciences, 2026)
The polluted coastal waters of Tripoli, Libya, driven by untreated sewage, pose significant health risks. This study investigated histopathological alterations in the kidneys and spleens, and isolated and identified multidrug-resistant bacteria from the kidneys of 20 Mugil cephalus specimens collected from anthropogenically stressed sites along the Tripoli coastline. Kidney tissues showed severe tubular necrosis, hyaline casts, glomerular atrophy, and interstitial mononuclear infiltration, while splenic tissues exhibited marked activation of the melanomacrophage centres (MMCs), vascular congestion, and multifocal granulomas. Bacteriological analysis of kidney homogenates detected growth in 60% of samples (mean 4.2 × 10⁵ CFU/g), predominantly multidrug-resistant Enterobacteriaceae (91.7% MDR), including Proteus vulgaris and Enterobacter cloacae. These findings demonstrate an association between antibiotic-resistant bacteria and chronic tissue damage, with MDR profiles indicating potential zoonotic transmission. The identified lesions may serve as bioindicators for monitoring drug-resistant microbes, underscoring the urgent need for wastewater treatment and surveillance to protect marine ecosystems and public health.